The Correlation of Anxiety in Postpartum Mothers During Covid-19 Pandemic With Breast Milk Expression - Izzah, Laili Nur; Sa'adii, Ashon; Ningtyas, Woro Setia (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2022)
Background: The COVID-19 pandemic has had a negative impact on people's psychology, such as panic disorder, stress, anxiety, and depression. Anxiety can affect the production of breast milk produced by the mother. The concentration of inhibiting and stimulating factors in the lactation process is influenced by various external stimuli such as baby sucking, the sound of a baby crying, and stress which is the impact of anxiety. The purpose of this study was to study and determine the relationship of anxiety in postpartum mothers during the COVID-19 pandemic with breastfeeding in Sekaran Lamongan Public Health CenterMethods: This type of research is analytic observational with a cross-sectional research design. The samples in this study were all populations that met all inclusion and exclusion criteria with a sampling technique using a non-probability sampling method with a purposive sampling technique. The independent variable of this study is anxiety and the dependent variable studied in this study is breast milk release.Results: Based on the results of this study, it was found that anxiety during the COVID-19 pandemic in 31 postpartum mothers in the working area of the Sekaran Lamongan Health Center, most of them did not experience anxiety as many as 23 people (74.2%) and most of them experienced smooth breastfeeding as many as 21 people ( 67.7%). The results of the bivariate analysis obtained a significance value of (p) = 0.000 which means the value is <0.05, so there is a relationship between anxiety in postpartum mothers during the COVID-19 pandemic and breastfeeding. The correlation value between the two variables obtained a value of (r) = -0.697 which indicates that the anxiety variable in postpartum mothers during the COVID-19 pandemic with breastfeeding has a strong relationship.Conclusion: The majority of respondents who do not experience anxiety during the COVID-19 pandemic will experience smooth breastfeeding, and there is a relationship between anxiety in postpartum mothers during the COVID-19 pandemic and breastfeeding at the Sekaran Lamongan Health Center.